PRISMA-Equity 2012 Extension: Reporting Guidelines for Systematic Reviews with a Focus on Health Equity - Welch, Vivian (Public Library of Science, 2012)
Vivian Welch and colleagues present consensus-based guidelines for reporting equity-focused systematic reviews, the PRISMA-Equity extension.